2022
DOI: 10.1111/jdi.13755
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of laparoscopic sleeve gastrectomy on obstructive sleep apnea and relationship of type 2 diabetes in Japanese patients with severe obesity

Abstract: Aims/Introduction Obstructive sleep apnea (OSA) is among the most important obesity‐related diseases, and offers the potential for accelerated the early onset and progression of type 2 diabetes. The aim of the present study was to clarify the therapeutic effect of laparoscopic sleeve gastrectomy on OSA in severely obese Japanese patients, and to find correlations between OSA improvements and β‐cell function (BCF). Materials and Methods Between September 2013 and December 2019, 61 patients who underwent laparos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 41 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…The six studies are summarized in Table 1 . Yanari et al 17 and Morong et al 26 were retrospective studies. The other four studies, de Raaff et al, 27 Peromaa-Havisto et al, 20 Haines et al, 28 and Ravesloot et al, 29 were prospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The six studies are summarized in Table 1 . Yanari et al 17 and Morong et al 26 were retrospective studies. The other four studies, de Raaff et al, 27 Peromaa-Havisto et al, 20 Haines et al, 28 and Ravesloot et al, 29 were prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical procedures were Roux-en-Y gastric bypass (RYGB) for de Raaff et al, 27 Peromaa-Havisto et al, 20 and Haines et al, 28 sleeve gastrectomy (SG) for Yanari et al, 17 and Ravesloot et al 29 compared laparoscopic gastric banding (LAGB) vs RYGB vs SG. In one study, the applied surgery was not reported (Morong et al 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations